Cytotoxin-producing Klebsiella oxytoca in the preterm gut and its association with necrotizing enterocolitis. Issue 1 (1st January 2020) - Paveglio, Sara; Ledala, Nagender; Rezaul, Karim; Lin, Qingqi; Zhou, Yanjiao; Provatas, Anthony A.; Bennett, Erin; Lindberg, Tristan; Caimano, Melissa; Matson, Adam P.
ABSTRACT: Necrotizing enterocolitis (NEC) is a devastating intestinal inflammatory disease of premature infants associated with gut bacterial dysbiosis. Using 16S rRNA-based methods, our laboratory identified an unclassified Enterobacteriaceae sequence (NEC_unk_OTU) with high abundance in NEC fecal samples. We aimed to identify this bacterium and determine its potential role in the disease. NCBI database searches for the 16S sequence, selective culture systems, biotyping and polymerase chain reaction were employed to refine classification of NEC_unk_OTU and identify toxin-encoding genes from the index NEC case. Bacterial cytotoxin production was confirmed by mass spectrometry and apoptosis assays. Additional fecal samples from 9 NEC and 5 non-NEC controls were analyzed using similar methods and multi-locus sequence typing (MLST) was performed to investigate clonal relationships and define sequence types of the isolates. NEC_unk_OTU was identified as Klebsiella oxytoca, a pathobiont known to cause antibiotic-associated hemorrhagic colitis, but not previously linked to NEC. Including the index case, cytotoxin-producing strains of K. oxytoca were isolated from 6 of 10 subjects with NEC; in these, the K. oxytoca 16S sequence predominated the fecal microbiota. Cytotoxin-producing strains of K. oxytoca also were isolated from 4 of 5 controls; in these, however, the abundance of the corresponding 16S sequence was very low. MLST analysis of the toxin-positive isolates demonstrated no clonal relationships and similar genetic clustering between cases and controls. These results suggest cytotoxin-producing strains of K. oxytoca colonize a substantial proportion of premature infants. Some, perhaps many, cases of NEC may be precipitated by outgrowth of this opportunistic pathogen.